2017
DOI: 10.3389/fneur.2017.00416
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Motor Impairments in Patients with Cerebral Palsy: Acute Effects of Whole-body Vibration on Stretch Reflex Response, Voluntary Muscle Activation and Mobility

Abstract: IntroductionIndividuals suffering from cerebral palsy (CP) often have involuntary, reflex-evoked muscle activity resulting in spastic hyperreflexia. Whole-body vibration (WBV) has been demonstrated to reduce reflex activity in healthy subjects, but evidence in CP patients is still limited. Therefore, this study aimed to establish the acute neuromuscular and kinematic effects of WBV in subjects with spastic CP.Methods44 children with spastic CP were tested on neuromuscular activation and kinematics before and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…In the present study, significant changes in the electromyographic signal of the VL muscle on both legs were observed in the acute effect of the last session of the 5-week WBVE intervention (Table 6). This is in agreement with other authors that have shown improvement in muscle activity due to WBVE intervention in different muscles in individuals with various diseases [27], such as acute and chronic stroke [30,56], spinal cord injury [24], Friedreich's ataxia [57], and cerebral palsy [29]. Liao et al detected changes in muscle activity even in individuals with paresis [30].…”
Section: Effect Of Wbve On Semgsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, significant changes in the electromyographic signal of the VL muscle on both legs were observed in the acute effect of the last session of the 5-week WBVE intervention (Table 6). This is in agreement with other authors that have shown improvement in muscle activity due to WBVE intervention in different muscles in individuals with various diseases [27], such as acute and chronic stroke [30,56], spinal cord injury [24], Friedreich's ataxia [57], and cerebral palsy [29]. Liao et al detected changes in muscle activity even in individuals with paresis [30].…”
Section: Effect Of Wbve On Semgsupporting
confidence: 91%
“…Yang et al concluded that WBVE increased the flexibility of the ankle joint, reduced the fear of falling, and strengthened the bones [38]. Although Krause et al observed no changes in the ankle joint excursion immediately after a 1-min bout of WBVE, they found an increase in the knee joint active angular excursion during flexion and extension (p < 0.01) in individuals with cerebral palsy [29]. In another study performed in children with cerebral palsy, a significant increase in ROM was detected immediately after treatment with WBVE [44].…”
Section: Effect Of Whole Body Vibration Exercise (Wbve) On Range Of Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as a mode of physical activity, WBVE has been identified as a feasible intervention with little to no adverse events [ 19 , 20 ]. WBVE has progressively been applied with beneficial outcomes to various clinical populations including stroke [ 7 , 21 ], obesity [ 22 ], rheumatoid arthritis [ 23 ], diabetes [ 24 ], spinal cord injury [ 25 ], chronic kidney disease [ 26 ], fibromyalgia [ 27 , 28 ], multiple sclerosis [ 29 ], cerebral palsy [ 30 , 31 ], Duchenne muscular dystrophy [ 32 ], osteogenesis imperfecta [ 33 ], osteoarthritis [ 34 ], and chronic obstructive pulmonary disease [ 35 ]. The effects of the WBVE may be due to neuromuscular responses to the interaction of the mechanical vibrations with the body and the tonic vibration response [ 36 – 39 ].…”
Section: Introductionmentioning
confidence: 99%